Dynamic mechanism and evolutionary game analysis of sports industry service transformation - Yihao Li; Xiaoyong Kou; Zhujun Li; Shaoyong Ye (Scientific Reports)
Abstract Service transformation plays a pivotal role in achieving the sustainable development of the sports industry. This study originates from the interactive relationships among sports enterprises, consumers, and regulatory authorities, proposing a logical framework for the service transformation of the sports industry. Furthermore, a three-party evolutionary game model is constructed to explore the strategic evolution and stability conditions under both single-agent and multi-agent scenarios. The primary findings are as follows: (1) Interactive relationships among sports enterprises, consumers, and regulatory authorities exhibit a game dilemma resembling the "prisoner’s dilemma." (2) A positive promotion relationship conducive to the transformation of the sports industry towards a service model is triggered only when at least two stakeholders’ strategic choices surpass a certain threshold. (3) Fiscal subsidies play a facilitating role in encouraging service transformation for sports enterprises but have limited incentives for consumers. Finally, this paper suggests the introduction of competition mechanisms and the establishment of reward and penalty systems, offering decision-making guidance for the service transformation of the sports industry.